Answer:
9
Step-by-step explanation:
-3+6 is 3
3*3 is 9
Answer:
Step-by-step explanation:
44b-33
Answer:
B = (2, -5)
Step-by-step explanation:
The problem requirements mean ...
B - A = (2/3)(C - A)
B = A + (2/3)C - A
B = (1/3)A + (2/3)C = (A +2C)/3
B = ((-6, 1) +2(6, -8))/3 = (-6+12, 1-16)/3 = (6, -15)/3
B = (2, -5)
10 - 5
10x + 5
10 + 5
We have that
From the expressions
The correct expression is
From the question we are told
Which of the following expressions has a coefficient of 10 and a constant of 5?
Generally
We Know That the coefficient of an expression precedes the main variable of the expression
While
The Constant is a Number that stands alone
Therefore
From the expressions
The correct expression is
For more information on this visit
Answer:
It would go down and then left and up
Answer:
c. x= 76, y= 63, z= 104
Step-by-step explanation:
First, you have to use the InteriorAnglesTheorem[m<1 + m<2 + m<3 = 180°] to find the m<x:
46° + 58° + 76° = 180°
Now that you have the m<x, to find the m<z, you have to use the SupplementaryAnglesTheorem,which statesthat two angles [in this case] add up to 180°:
76° + 104° = 180°
Finally, to find the m<y, you again have to use the InteriorAnglesTheorem:
13° + 63° + 104° = 180°
If you are ever in need of assistance, do not hesitate to let me know by subscribing to my You-Tube channel [USERNAME: MATHEMATICS WIZARD], and as always, I am joyous to assist anyone at any time.